1971
DOI: 10.1002/bjs.1800581203
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm of an anomalous hepatic artery

Abstract: successfully treated by prosthetic grafting is reported. This appears to be the forty-third patient to survive surs&al treatment for this condition. HeDatic arterv here has been managed by resection of the aneurysm The third of hepatic artery aneurysm and replacement with a Dacron prosthesis. The from an anomalous Position On the front of the aorta beneath the duodenojejunal aneurysm has a poor prognosis and operative treatment is justified when the diagnosis is made. While ligation will be required in some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For surgical hepatic artery aneurysm repair many techniques have been described including restorative endo-aneurysmorhaphy, excision and end-to-end anastomosis, splenohepatic anastomosis, interposition of a prosthetic graft [19] and interposition of autogenous saphenous vein performed with good results in the past three decades [5,17,18,24,29]. The aneurysm of the patient of the current study was repaired with autologous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For surgical hepatic artery aneurysm repair many techniques have been described including restorative endo-aneurysmorhaphy, excision and end-to-end anastomosis, splenohepatic anastomosis, interposition of a prosthetic graft [19] and interposition of autogenous saphenous vein performed with good results in the past three decades [5,17,18,24,29]. The aneurysm of the patient of the current study was repaired with autologous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…7 This complication was described in detail along with the surgical procedure used to treat the condition by Ariyan et al 7 Of the 47 successful cases the researchers found, the majority were treated with ligation, followed by excision, endoaneurysmorrhaphy, wrapping, wiring, hepatic lobectomy, and suturing of the aneurysm. 4,7,[17][18][19][20][21][22][23][24][25] In 1986 Curran and Taylor 9 reported that there had been 300 cases of HAA, but still only 20 per cent had been treated successfully. 4,7,26 This review also stated that atherosclerosis accounted for 32 per cent of HAA cases.…”
mentioning
confidence: 99%